Penguatan Kelompok Usaha Tani Berbasiskan Pemberdayaan Masyarakat Petani Padi - Paul Adryani Moento; Rangga Kusumah; Apolus Betaubun; Hubertus Oja (Universitas Musamus, Merauke, Papua, 2020)
The purpose of this study is to analyze the Government's Program in Strengthening Farmer BusinessGroups Based on the Empowerment of Rice Farmers Communities. The method used to achieve the goalis to provide education to the rice farming community based on farming groups. The research uses aqualitative approach, while data collection techniques consist of literature study and field studies throughobservation, interviews. The data analysis process includes data reduction, data presentation, anddrawing conclusions. The results in the field stated that the socialization was carried out to provideunderstanding to farmer groups in kuprik village to challenge how to develop an agricultural program,then PPL Officers conducted field supervision to farmer groups, by providing motivation and structureddirection on how to obtain and manage quality harvests. . Then PPL officers also analyze the problemsthat occur in kuprik village agricultural land, a problem that they can continue to the agriculturedepartment to find solutions in order to create quality crops. Furthermore, the marketing facilities forrice harvest from farmers are not provided by the government. The harvest from the farmers communityin Kampung Kuprik is sold alone